1995
DOI: 10.1063/1.470148
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transitions of cobalt carbide, CoC, near 750 nm: A good example of case (bβS) hyperfine coupling

Abstract: The laser induced fluorescence spectrum of jet-cooled CoC near 750 nm has been measured at high resolution following the reaction of laser-ablated cobalt atoms with methane. The X 2 ⌺ ϩ ground state of CoC is an unusually good example of Hund's case (b ␤S ) coupling. Since Co has a nuclear spin Iϭ7/2, each rotational level is split by the Fermi contact interaction into Gϭ3 and Gϭ4 components, where G‫؍‬I؉S; the splitting for Nϭ0 is more than 0.5 cm Ϫ1. The X 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 40 publications
8
82
0
Order By: Relevance
“…A cobalt target, in the form of a slowly rotating and translating solid rod, was ablated by about 3 mJ of 355 nm between 500 and 720 nm. Coincidentally, this system was observed while Barnes et al (2) were independently dis-radiation from a Nd:YAG laser. At the same time, a mixture of approximately 1.5% methanol or methane vapor in a hecovering the B 2 P-X 2 S / system near 760 nm.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…A cobalt target, in the form of a slowly rotating and translating solid rod, was ablated by about 3 mJ of 355 nm between 500 and 720 nm. Coincidentally, this system was observed while Barnes et al (2) were independently dis-radiation from a Nd:YAG laser. At the same time, a mixture of approximately 1.5% methanol or methane vapor in a hecovering the B 2 P-X 2 S / system near 760 nm.…”
Section: Methodsmentioning
confidence: 84%
“…The characterized. discovery and rotational analysis of FeC has been reported by Balfour et al (1) while cobalt monocarbide has been recently reported on by Barnes et al (2), who analyzed…”
Section: Introductionmentioning
confidence: 89%
“…. 3π 4 1δ 4 9σ 1 configuration and the 9σ and 1δ orbitals were shown to be primarily metal 4s and 3d in character, respectively (12,13), from the analysis of the hyperfine structure. system in the diode laser investigation which will be described later.…”
Section: Other New Bands In Connection With the Excited States Reportmentioning
confidence: 99%
“…While the electronic spectra of the 3d transition metal oxides have been studied extensively, very little has been published on the 3d transition metal carbides. The gas phase spectroscopic studies have been published only for FeC (6)(7)(8)(9) and CoC (10,11). The electronic spectrum of FeC is complicated due to many perturbations, as has been found in the later 3d transition metal oxides such as FeO (12,13) and CoO (14).…”
Section: Introductionmentioning
confidence: 98%
“…It is useful to refer to the previous studies of CoC (10,11) for which the electronic structure is relatively well understood by hyperfine analyses, because we can expect similar molecular orbitals for FeC states also do not arise from the configuration (D) for which the largest internuclear distance is expected. From these considerations, the configuration of the [13.17] 3 state is the one for which the internuclear distance is largest of the configurations (A)-(C).…”
mentioning
confidence: 98%